Energy Efficient Optimized Sleep Scheduling Routing Protocol for Enhancement of MANET Lifetime - Kumar, Veepin; Singla, Sanjay; Arora, Shalika; Keshari, Surendra Kumar; Kumar, Sanjeev (Wireless personal communications, 2024)
Mobile Ad hoc Network (MANET) is an infrastructure-less network of mobile nodes which used in military, rescue operations, disaster relief, and rural areas for communications. To process the data packets, MANET nodes consume a lot of energy during real time data transmission. The conventional protocol selects the random route path in the network. Due to overhead in the random route path the power consumptions may exhaust the energy of nodes which causes the communication delay or may path failure. To address these issues an optimized energy efficient routing protocol could be used which prevents excessive consumption of node energy and enhances the network lifespan. In our research work, a novel nature-inspired Energy Efficient Optimized Sleep Scheduling (EEOSS) protocol is proposed to enhance the effectiveness and increase lifetime of ad hoc network. EEOSS protocol is the hybridization of ad hoc on-demand multi-path distance vector (AOMDV), Ant colony optimization (ACO), Particle swarm optimization (PSO) and sleep scheduling (SS) algorithms. AOMDV selects the multiple paths for data transmission whereas, ACO and PSO are used to identify the optimum route path based on number of nodes, packet size and node speed. To save the energy of nodes the SS algorithm puts nodes into sleep state when nodes are not participating actively in the network. The suggested protocol is compared experimentally with other existing routing protocols and measures performance based on throughput, energy consumption, end-to-end delay (E2ED), and network lifetime. The experiments are simulated on NS 2.35 and the results find that the EEOSS protocol has 12% improvement in throughput, 18% improvement in network lifetime, 12% improvement in E2ED and 9% improvement for energy consumption as compare to other state of art.